Analysis of Student Experience in Using Building Information Modeling (BIM) to Understand the Concept of Steel Structure - Muhammad Raihansyah Muhadzib; M. Agphin Ramadhan; Arris Maulana; Galeh Nur Indriatno Putra Pratama (Universitas Negeri Yogyakarta, 2025)
Background: BIM is a digital program or software that was created to transform the conventional construction world into a digital and integrated construction world to facilitate development work. This study aims to determine the experience of students in using BIM to understand the concept of Steel Structures for students of classes 2020 & 2021. Methods: This research uses a qualitative approach with thematic analysis techniques, whose data collection uses BIM test scores and Steel Structure II scores. Data collection techniques were carried out by interviewing 10 students who could do the BIM test and get high Steel Structure scores. Thematic analysis using ChatGPT version 4. Results: The results show that there are 6 themes in the experience of students in using BIM to understand the concept of Steel Structure. The first theme is the general experience with BIM. The second theme is the benefits of using BIM for Steel Structures. The third theme was the challenges in using BIM, and students experienced initial difficulties in understanding BIM. The fourth theme was the role of BIM in improving understanding of Steel Structures. The fifth theme is the perception of using BIM in civil engineering learning. The sixth theme is suggestions for improving the use of BIM. Conclusion: This research concludes that the use of BIM in learning Steel Structure is very useful to deepen students' understanding of the concept of Steel Structure.